2000
DOI: 10.1021/bi000178y
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Interpretation of Nitrite Reduction by Cytochrome cd1 Nitrite Reductase from Paracoccus pantotrophus

Abstract: The reduction of nitrite to nitric oxide in respiratory denitrification is catalyzed by a cytochrome cd(1) nitrite reductase in Paracoccus pantotrophus (formerly known as Thiosphaera pantotropha LMD 92.63). High-resolution structures are available for the fully oxidized [Fülöp, V., Moir, J. W., Ferguson, S. J., and Hajdu, J. (1995) Cell 81, 369-377; Baker, S. C., Saunders, N. F., Willis, A. C., Ferguson, S. J., Hajdu, J., and Fülöp, V. (1997) J. Mol. Biol. 269, 440-455] and fully reduced forms of this enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…We thus propose that substitution of either one of the two invariant active-site His with Ala and reduction of the positive potential in the pocket is associated with loss of the hydroxyl, which was found to be coordinated with the ferric d 1 -heme iron in the wt enzyme (4) and should assist NO dissociation. This hypothesis is in agreement with quantum mechanical calculations (29), indicating that interaction with the active-site His can stabilize and orient nucleophilic ligands of the d 1 -heme, the presence of which imposes an unfavorable orientation on NO and thereby facilitates its release. It is worth noting that it has been recently shown that a buried carboxylate in the active site of nitrophorins (a class of heme proteins with vasodilatory activity associated with NO release) promotes dissociation of NO from the ferric heme iron (30).…”
Section: Discussionsupporting
confidence: 89%
“…We thus propose that substitution of either one of the two invariant active-site His with Ala and reduction of the positive potential in the pocket is associated with loss of the hydroxyl, which was found to be coordinated with the ferric d 1 -heme iron in the wt enzyme (4) and should assist NO dissociation. This hypothesis is in agreement with quantum mechanical calculations (29), indicating that interaction with the active-site His can stabilize and orient nucleophilic ligands of the d 1 -heme, the presence of which imposes an unfavorable orientation on NO and thereby facilitates its release. It is worth noting that it has been recently shown that a buried carboxylate in the active site of nitrophorins (a class of heme proteins with vasodilatory activity associated with NO release) promotes dissociation of NO from the ferric heme iron (30).…”
Section: Discussionsupporting
confidence: 89%
“…the movement of the tethered shuttle protein) either in catalysis (2,4,27) or in the control of catalysis (4,5,11,27). Although the presence of alternative conformers of NiR has long been a subject of speculation, the dramatic alteration in relative domain arrangement compared with the previously known structures was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still possible, for example, that approach of tyrosine 25 toward the two active-site histidine residues (positions 345 and 388) plays a role in driving dissociation of nitric oxide (17) and that this role can be replicated by the hydroxy group of serine 25. In other words, as discussed elsewhere (17) (17).…”
Section: Significance Of Tyrosine 25 Binding To the D 1 Heme Iron-mentioning
confidence: 99%
“…17). Structures of cytochrome cd 1 from crystals that had first been reduced and then treated with nitrite showed tyrosine 25 apparently poised ready to displace a bound nitric oxide (9); the significance of this residue, but not necessarily its religation to the d 1 heme iron, for this displacement has been indicated by calculations (17). The driving force for tyrosine 25 to ligate to the oxidized iron of the d 1 heme is certainly large.…”
mentioning
confidence: 98%